Genetic Variation of Kallikrein-Kinin System and Related Genes in Patients With Hereditary Angioedema - Veronez, Camila Lopes; Aabom, Anne; Martin, Renan Paulo; Filippelli-Silva, Rafael; Gonçalves, Rozana Fátima; Nicolicht, Priscila; Mendes, Agatha Ribeiro; Da Silva, Jane; Guilarte, Mar; Grumach, Anete Sevciovic; Mansour, Eli; Bygum, Anette; et al. (Frontiers in Medicine, 2019)
Hereditary angioedema (HAE) is an autosomal dominant disease caused by C1-INH deficiency due to mutations in SERPING1 (C1-INH-HAE) in most of the cases, or by specific mutations in factor XII gene, F12 (F12-HAE). Identification of polymorphisms in the genes encoding proteins from key pathways driving HAE can help to understand how genetic diversity contributes to its phenotypic variability. Here, 15 genes related to the Kallikrein-Kinin System (KKS) were analyzed by next generation sequencing in 59 patients with C1-INH-HAE or F12-HAE from Brazil, Denmark and Spain, and 19 healthy relatives in a total of 31 families. We identified 211 variants, from which 23 occurred only in Danish subjects and 79 were found only in Brazilian individuals, resulting in 109/211 variations in common between European and Brazilian population in the HAE families analyzed. BDKRB2 and CPM presented a large number of variants in untranslated regions, 46/49 and 19/24, respectively; whereas ACE (n=26), SERPING1 (n=26), CPM (n=24), and NOS3 (n=16) genes presented the higher number of variants directly affecting amino acid sequence. Despite the large amount of variants identified, the lack of association between genotype and phenotype indicates that the modulation of HAE symptom requires a more complex regulation, probably involving pathways beyond the KKS, epigenetics and environmental factors. Considering the new HAE types recently described, molecules involved in the regulation of vasculature and in plasminogen activation become promising targets for future genetic studies.